The actions for carbon neutrality in the social network of supply chains - Weifeng Zhai; Shujuan Zhang; Yan Zhang; Xuewen Zhang; Hongyan Yang (Carbon Management)
By integrating social network theory and signaling theory, this paper investigates the actions for carbon neutrality in the social network of supply chains. We consider the actions for carbon neutrality by a focal actor as signaling its intent and ability to efficiently reduce carbon emission to supply chain members. The empirical test shows that four measurements of actors’ position in a social network, i.e. closeness centrality, betweenness centrality, eigenvector centrality and structural holes, positively and significantly influence the actions for carbon neutrality. The results of empirical test indicate that carbon reduction through supply chains is an effective and systematic method for carbon neutrality.